2014
DOI: 10.1128/jvi.00202-14
|View full text |Cite
|
Sign up to set email alerts
|

Reinitiation after Translation of Two Upstream Open Reading Frames (ORF) Governs Expression of the ORF35-37 Kaposi's Sarcoma-Associated Herpesvirus Polycistronic mRNA

Abstract: bThe Kaposi's sarcoma-associated herpesvirus (KSHV) ORF36 protein kinase is translated as a downstream gene from the ORF35-37 polycistronic mRNA via a unique mechanism involving short upstream open reading frames (uORFs) located in the 5= untranslated region. Here, we confirm that ORF35-37 is functionally dicistronic during infection and demonstrate that mutation of the dominant uORF restricts KSHV replication. Leaky scanning past the uORFs facilitates ORF35 expression, while a reinitiation mechanism after tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…uORFs are known to have roles in translation regulation during stress [104]. Translation of the uORF that overlaps with the start codon of ORF35 prevents ORF35 translation and instead promotes ribosome engagement of the ORF36 start codon, which is downstream of the uORF stop codon, through a non-canonical mechanism of translation reinitiation [103, 105]. Because of inherent variability in engagement of the start codons, ORF35 expression from the transcript is lower than ORF36 expression, but not absent [103, 105].…”
Section: Post-transcriptional Control Of Viral Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…uORFs are known to have roles in translation regulation during stress [104]. Translation of the uORF that overlaps with the start codon of ORF35 prevents ORF35 translation and instead promotes ribosome engagement of the ORF36 start codon, which is downstream of the uORF stop codon, through a non-canonical mechanism of translation reinitiation [103, 105]. Because of inherent variability in engagement of the start codons, ORF35 expression from the transcript is lower than ORF36 expression, but not absent [103, 105].…”
Section: Post-transcriptional Control Of Viral Gene Expressionmentioning
confidence: 99%
“…Translation of the uORF that overlaps with the start codon of ORF35 prevents ORF35 translation and instead promotes ribosome engagement of the ORF36 start codon, which is downstream of the uORF stop codon, through a non-canonical mechanism of translation reinitiation [103, 105]. Because of inherent variability in engagement of the start codons, ORF35 expression from the transcript is lower than ORF36 expression, but not absent [103, 105]. The recent ribosome profiling of the KSHV genome revealed that other KSHV mRNAs also have uORFs in their 5’ UTRs that appear to be actively translated [15], but it is not known whether they also have regulatory functions on the expression of viral proteins or facilitate expression of multiple proteins from polycistronic transcripts.…”
Section: Post-transcriptional Control Of Viral Gene Expressionmentioning
confidence: 99%
“…In this regard, the ability of uORFs to render mRNAs functionally polycistronic has been documented for the KSHV ORF35–37 locus. Translation of both ORF35 (which encodes a protein of unknown function) and the downstream ORF36 (which encodes the viral protein kinase) occurs from the same mRNA, whereas ORF37 is expressed from a distinct monocistronic transcript (117, 118). The polycistronic mRNA contains two uORFs within its 5′ mRNA leader sequence, the second of which (uORF2) overlaps with the ORF35 start codon.…”
Section: Expansion and Regulation Of Viral Coding Capacity Through Upmentioning
confidence: 99%
“…Although ORF35 AUG is flanked by a strong Kozak consensus sequence, translational engagement of the overlapping uORF2 allows ribosomes to frequently bypass ORF35 AUG and reinitiate at the downstream ORF36 gene (117). Translation of the 5′-most uORF1 further reduces ribosome engagement at ORF35 AUG , resulting in fairly balanced initiation rates for both ORF35 and ORF36 from the same mRNA by leaky scanning and termination-reinitiation mechanisms, respectively (118). …”
Section: Expansion and Regulation Of Viral Coding Capacity Through Upmentioning
confidence: 99%
“…The translation of one of the 5′ distal gene ORF71 (vFLIP) is mediated by an internal ribosomal entry mechanism [6466]. Hypoxia-induced polycistronic transcripts ORF34/35/36/37 encode two short upstream ORFs, uORF35.1 and uORF35.2, within the 5′ leader sequence of the ORF35–36 bicistronic transcript [6769]. Both uORFs function as negative regulators of ORF35 while the second one allows the translation of the downstream ORF36 gene by a termination-reinitiation mechanism [67,68].…”
Section: Introductionmentioning
confidence: 99%